Manajemen Pembinaan dan Latihan Bulutangkis Siswa SD Negeri 2 Barongan Kudus: Badminton Management and Training for Students in SD Negeri 2 Barongan Kudus - Aryanti, Risti; Lismadiana, Lismadiana (Universitas Muhammadiyah Sidoarjo, 2019)
This research aims to describe (1) planning, (2) organizing, (3) actuating, and (4) controllings process in the implementation of management coaching and training. The research method in this study used qualitative descriptive method. The techniques used unstructured interview and documentation. The validity of the data was used credibility test with triangulation of technique, source, and time. Data analysis techniques used the interactive analysis model Miles and Huberman include the stages of data collection, data reduction, data presentation, and conclusion / verification. The results of the study show that: (1) planning was carried out in coordination with all management to establish the program. (2) Organizing was carried out in collaboration with between th teacher and students in practicing. (3) Actuating was carried out with students following a number of exercises based on the time schedule. (4) Supervision was carried out to evaluate all programs that have been implemented.